Principles, applications, and future of artificial intelligence in dermatology - Omiye, Jesutofunmi A.; Gui, Haiwen; Daneshjou, Roxana; Cai, Zhuo Ran; Muralidharan, Vijaytha (Frontiers in Medicine, 2023)
This paper provides an overview of artificial-intelligence (AI), as applied to dermatology. We focus our discussion on methodology, AI applications for various skin diseases, limitations, and future opportunities. We review how the current image-based models are being implemented in dermatology across disease subsets, and highlight the challenges facing widespread adoption.Additionally, we discuss how the future of AI in dermatology might evolve and the emerging paradigm of large language, and multi-modal models to emphasize the importance of developing responsible, fair, and equitable models in dermatology.